The church history of Rufinus of Aquileia, books 10 and 11 - Rufinus, of Aquileia, 345-410 (Oxford University Press, 1997)
Amidon offers the first English translation of Books 10 and 11 of Rufinus' Church History. Books 1-9 comprise a Latin translation of Eusebius' history. Books 10 and 11 are Rufinus' own continuation, covering the period 325-395. As the first Latin church history, this work exerted great influence over the subsequent scholarship of the Western Church.